Analysis Strategy by Priority Rate using ANP for Pension Fund Organization - Arifman Afda; Cutifa Safitri (Journal of Accounting and Finance Management, 2026)
A pension fund organization is a corporation that manages and implements a program that provides benefits of pensions. One of the reasons why pension fund organizations don’t grow significantly is because the masses still don’t believe that organizations should implement a pension program. More important, their fund is not left. Pension Fund needs an information technology solution. For efficiency, using the method of Strategic Planning for Information Systems (SPIS), it’s mean calculations about external or internal factors in the organizational environment to generate the weight of value. The weight of all factors and strategies is using Analytical Hierarchy Processing (AHP). Every factor that has a relationship will be analyzed by the SWOT method (Strength, Weakness, Opportunities, Threats). The result will be processed by prioritizing strategies for all business processes and information systems that use the ANP method (analytical network processing). In this research, the ANP methods combining with ZOGP (Zero One Goal Programing) to increase the result with resources calculations. At last, Weight of business processing and information system will be calculated by the IT Balanced Score based on the priority rate. This research will help pension fund organizations choose an information system strategy to develop an information system or application to reach the best goal.